The Effects of Avocado Waste and Its Functional Compounds in Animal Models on Dyslipidemia Parameters - Pineda-Lozano, Jessica Elizabeth; Martínez-Moreno, Alma Gabriela; Virgen-Carrillo, Carmen Alejandrina (Frontiers in Nutrition, 2021)
Ischemic heart disease and stroke are two main causes of death that have prevailed for more than 15 years. Dyslipidemia and its parameters like hypercholesterolemia, hypertriglyceridemia, increase in low-density cholesterol, and a reduction of high-density cholesterol have been related with heart disease and risk of stroke. Approaches to improve the health and specifically reduce the risk of heart disease, such as medications and dietary interventions have been effective, but there are other potential sources of biological compounds that could have an effect due to their antioxidant properties. Avocado is a commonly consumed fruit especially its pulp, while the peel, seed, and leaf are usually discarded as waste. Some researchers have reported antioxidant, hepatoprotective, gastroprotective, lipid-lowering, and hypoglycemic effects in these wastes. In this review article, we have summarized the current evidence on the effect of biological compounds from avocado waste on dyslipidemia parameters in preclinical models. Also, we have included the compound extracted and the extraction method from the selected articles.